IRECIST: guidelines for response criteria for use in trials testing immunotherapeutics. Issue 3 (March 2017) - Seymour, Lesley; Bogaerts, Jan; Perrone, Andrea; Ford, Robert; Schwartz, Lawrence H; Mandrekar, Sumithra; Lin, Nancy U; Litière, Saskia; Dancey, Janet; Chen, Alice; Hodi, F Stephen; Therasse, Patrick; et al.
Summary: Tumours respond differently to immunotherapies compared with chemotherapeutic drugs, raising questions about the assessment of changes in tumour burden—a mainstay of evaluation of cancer therapeutics that provides key information about objective response and disease progression. A consensus guideline—iRECIST—was developed by the RECIST working group for the use of modified Response Evaluation Criteria in Solid Tumours (RECIST version 1.1) in cancer immunotherapy trials, to ensure consistent design and data collection, facilitate the ongoing collection of trial data, and ultimate validation of the guideline. This guideline describes a standard approach to solid tumour measurements and definitions for objective change in tumour size for use in trials in which an immunotherapy is used. Additionally, it defines the minimum datapoints required from future trials and those currently in development to facilitate the compilation of a data warehouse to use to later validate iRECIST. An unprecedented number of trials have been done, initiated, or are planned to test new immune modulators for cancer therapy using a variety of modified response criteria. This guideline will allow consistent conduct, interpretation, and analysis of trials of immunotherapies.